2020
DOI: 10.1111/phn.12761
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for sperm‐targeted contraception: College students’ perceptions and intentions related to non‐hormonal intravas injectable gel

Abstract: Objective The objective of the study was to evaluate college students’ perceptions and behavioral intentions related to a new long‐acting reversible contraceptive (LARC) for people with penises: non‐hormonal intravas injectable gel (NH‐IVIG). Design and Sample Data collection utilized predictive constructs from the theory of planned behavior. An online questionnaire surveyed undergraduates (ages 18–24 years) at a Midwestern, liberal arts college (N = 460). Results Of potential NH‐IVIG users, 28.6% of males and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Three recent U.S.-based studies have examined men’s willingness to use MBC, all among young men. In two surveys of male undergraduate students, 35% reported high willingness to try male hormonal contraception [ 6 ] and only 29% were likely to use vas occlusion, specifically [ 5 ]. In a combined sample of students and clinic attendees aged 18–35, 45% of men were willing to use MBC [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three recent U.S.-based studies have examined men’s willingness to use MBC, all among young men. In two surveys of male undergraduate students, 35% reported high willingness to try male hormonal contraception [ 6 ] and only 29% were likely to use vas occlusion, specifically [ 5 ]. In a combined sample of students and clinic attendees aged 18–35, 45% of men were willing to use MBC [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…High cost was another potential barrier cited by the majority of our participants. Some prior studies have found cost to be a salient consideration among potential MBC users [ 5 , 22 ] while others [ 7 ] have not. Future work may identify the thresholds at which men consider MBC to be affordable versus cost-prohibitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…inhibition of sperm under guidance (RISUG)", which have reached clinical trials in men. 21,22 The principle of the RISUG strategy is to physically block the vas deferens using a hydrogel and prevent sperm from passing through, which shows a 97.3% contraceptive rate. 23 Unsatisfactorily, the RISUG hydrogel can only be removed by in situ injection of dimethyl sulfoxide (DMSO), which is a highly toxic organic solvent that can cause some side effects in the human body.…”
mentioning
confidence: 99%
“…In recent years, hydrogel materials have been applied in a reversible male contraceptive method, called “reversible inhibition of sperm under guidance (RISUG)”, which have reached clinical trials in men. , The principle of the RISUG strategy is to physically block the vas deferens using a hydrogel and prevent sperm from passing through, which shows a 97.3% contraceptive rate . Unsatisfactorily, the RISUG hydrogel can only be removed by in situ injection of dimethyl sulfoxide (DMSO), which is a highly toxic organic solvent that can cause some side effects in the human body. , In addition, a cocktail-inspired male contraceptive material that can be reversed by near-infrared light was proposed by Bao et al ., wherein four layers of reagents were injected sequentially into the vas deferens.…”
mentioning
confidence: 99%